Perbandingan Stabilitas Atmosfer di Permukaan Manifestasi Panas Bumi dengan Tanpa Manifestasi Panas Bumi menggunakan Bilangan Richardson - Andreas Panjaitan; Rolles Nixon Palilingan; Cyrke Adfie Netty Bujung; Sixtus Iwan Umboh (Jurnal FisTa : Fisika dan Terapannya, 2024)
The stability of the atmosphere can affect the weather conditions in an area. This study aims to compare atmospheric stability carried out in Lake Linow which has two surfaces, namely the surface of geothermal manifestation and the surface without geothermal manifestation. In determining the stability of the atmosphere, researchers use the Richardson number method. To determine atmospheric stability using the Richardson number, data on wind speed and temperature at each altitude are needed. The measured height is 2 meters and 4 meters from the surface. The results of this study show that on the surface geothermal manifestations have unstable atmospheric stability with Richardson numbers -1.4729 to -0.1420, while on the surface without geothermal manifestations have 3 states of atmospheric stability, namely: stable, neutral, and unstable, with Richardson numbers -1.1316 to 0.9808. Therefore, it can be concluded that the state of the atmosphere on the surface of geothermal manifestations is more unstable, compared to surfaces without geothermal manifestations.